Analysis of the Structure, Functions, and Values of Local Wisdom in the Folklore of Southeast Aceh Si Layakh with Brudinam - Sri Listiana Izar; Adira Oktaviani (Proceeding International Conference on Malay Identity, 2021)
Abstract: This study aims to describe the structure of the folklore of Si Layah and Brudinam and to find out the forms of local wisdom in the folklore of Si Layah and Brudinam. The data for this research is a folklore book entitled Si Layakh with Brudinam. This story comes from Southeast Aceh. The method used is descriptive qualitative method. The instrument used in this research is a documentation study. The analysis technique was carried out by describing the structure and local wisdom contained in the book of Southeast Acehnese folklore Si Layakh with Brudinam. The results of this study indicate that there is a link between the intrinsic structure and the form of local wisdom that builds the folklore of Si Layah and Brudinam. Keywords: Structural analysis, local wisdom, folklore of the worthy with brudinam